THE RELATIONSHIP BETWEEN CORPORATE ORIENTATION AND ICT MANAGEMENT IN HIGHER EDUCATION - Palilingan, Verry Ronny; Sumual, Syerri Yullita; Itje, Tomi (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
ICT management is a system that ensures the use of ICT is aligned with the organization's overall strategy and goals. Corporate orientation is understood as the application of modern governance principles such as efficiency, accountability, and professionalism in university management, but there are fundamental problems in the use of ICT. This study aims to analyze the relationship between corporate orientation and the management of Information and Communication Technology (ICT) in higher education through a case study at the University of Halmahera. This study uses a descriptive qualitative approach, with data collection techniques through interviews, observation of campus information systems, and document analysis. The data analysis technique in this study is Thematic Analysis. The results of the study show that corporate orientation contributes significantly in strengthening ICT management, especially in strategic planning, operational standards, data security, and information system integration. However, there are obstacles such as limited human resource competencies, uneven understanding of work culture, and limited technological infrastructure. This research emphasizes the importance of corporate orientation in supporting digital transformation and strengthening higher education ICT governance.